2022
DOI: 10.1038/s42003-022-03990-w
|View full text |Cite
|
Sign up to set email alerts
|

The Musashi proteins direct post-transcriptional control of protein expression and alternate exon splicing in vertebrate photoreceptors

Abstract: The Musashi proteins, MSI1 and MSI2, are conserved RNA binding proteins with a role in the maintenance and renewal of stem cells. Contrasting with this role, terminally differentiated photoreceptor cells express high levels of MSI1 and MSI2, pointing to a role for the two proteins in vision. Combined knockout of Msi1 and Msi2 in mature photoreceptor cells abrogated the retinal response to light and caused photoreceptor cell death. In photoreceptor cells the Musashi proteins perform distinct nuclear and cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Consistent with these functional enrichments, a zebrafish mutant for srrm3 , showing a large mis-regulation of RetMICs, exhibited severe OS alteration, photoreceptor death and blindness (Ciampi et al, 2022 ). However, despite the strong phenotype of a global microexon mis-regulation, it should be noted that depletion of individual RetMICs in mice have not shown any evident visual phenotypes (Matalkah et al, 2022 ), likely as a result of compensatory effects and the high robustness of living systems to relatively subtle perturbations as those exerted by individual microexon deletions.…”
Section: As In Retinal Photoreceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with these functional enrichments, a zebrafish mutant for srrm3 , showing a large mis-regulation of RetMICs, exhibited severe OS alteration, photoreceptor death and blindness (Ciampi et al, 2022 ). However, despite the strong phenotype of a global microexon mis-regulation, it should be noted that depletion of individual RetMICs in mice have not shown any evident visual phenotypes (Matalkah et al, 2022 ), likely as a result of compensatory effects and the high robustness of living systems to relatively subtle perturbations as those exerted by individual microexon deletions.…”
Section: As In Retinal Photoreceptorsmentioning
confidence: 99%
“…The patterns of AS in retina and photoreceptors are known to be in part driven by the direct action of an RNA-binding protein called Musashi-1 (MSI1) (Murphy et al, 2016 ; Ling et al, 2020 ; Matalkah et al, 2022 ). The Musashi family comprises two members, MSI1 and MSI2 , and it has been involved in stem cell renewal and negative regulation of cell differentiation.…”
Section: Assembling the Unique Srs Of Photoreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing to this is regulation at the post-transcriptional level -that involves non-coding RNA or RNA-binding protein (RBP)-mediated control over mRNA splicing, transport, stability and translation -all of which determines the cellular proteome (Brinegar and Cooper 2016;Hentze et al 2018;Gebauer et al 2021). Indeed, recent findings have demonstrated that RBPs play a conserved role in mediating post-transcriptional control in eye and lens development Lachke and Maas 2011;Dash et al 2015Dash et al , 2016Dash et al , 2020Siddam et al 2018;Shao et al 2020;Barnum et al 2020;Nakazawa et al 2020;Sundar et al 2020;Aryal et al 2020b;Lachke 2022;Matalkah et al 2022). Together, these findings suggest that along with the transcriptome, characterization of the proteome is important to determine the factors that are important in a specific cell/tissue of interest.…”
Section: Embryonic Combined Retina and Rpe Proteomementioning
confidence: 99%
“…H3K4me3 and H3K36me3 have been linked to the regulation of transcription initiation and elongation, respectively. Since photoreceptors experience age-associated changes in transcription factor activity 24 , 25 , as well as splicing 26 , 27 , we sought to study how histone methylation contributed to the aging transcriptome. Further, we wondered if decreasing levels of one of these active marks would directly contribute to any of the age-associated changes observed in the transcriptome of aging photoreceptors.…”
Section: Introductionmentioning
confidence: 99%